Genome-Wide Association Study on the Hematological Phenotypic Characteristics of the Han Population from Northwest China - Yang W; He X; Yao Y; Lu H; Wang Y; Zhang Z; Wang Y; Wang L; He Y; Yuan D; Jin T (Dove Medical Press, 2022)
Wei Yang,1- 3 Xue He,1,2 Yuying Yao,2 Hongyan Lu,2 Yuliang Wang,2 Zhanhao Zhang,2 Yuhe Wang,1,2,4 Li Wang,1,2 Yongjun He,1,2 Dongya Yuan,1,2 Tianbo Jin1,2 1Key Laboratory of Molecular Mechanism and Intervention Research for Plateau Diseases of Tibet Autonomous Region, School of Medicine, Xizang Minzu University, Xianyang, Shaanxi, 712082, People's Republic of China; 2School of Basic Medical Sciences, Xizang Minzu University, Xianyang, Shaanxi, 712082, People's Republic of China; 3Department of Emergency, The Affiliated Hospital of Xizang Minzu University, Xianyang, Shaanxi, 712082, People's Republic of China; 4Department of Clinical Laboratory, The Affiliated Hospital of Xizang Minzu University, Xianyang, Shaanxi, 712082, People's Republic of ChinaCorrespondence: Tianbo Jin, Key Laboratory of Molecular Mechanism and Intervention Research for Plateau Diseases of Tibet Autonomous Region, School of Medicine, Xizang Minzu University, #6 East Wenhui Road, Xianyang, Shaanxi, 712082, People's Republic of China, Tel/Fax +86-29-88895902, Email tianbo__jin@163.comBackground: Hematological characteristics have positive reference value as clinical indicators in the evaluation of various diseases. The purpose of this study was to determine the gene loci associated with 20 hematological phenotypes in the Han population from northwest China.Methods: A genome-wide association study (GWAS) was conducted on hematological indicators of 1005 Han people from northwest China. Genotyping was performed with a GeneTitan multichannel instrument and Axiom Analysis Suite 6.0. Using the 1000 Genomes Project (phase 3) as a reference, haplotype imputation was performed with IMPUTE2. SNVs (single nucleotide variants) significantly associated with hematological phenotypes were identified. The top SNV (p < 5E-7) was then selected for replication detection.Results: Ninety genetic variations identified in the GWAS were significantly associated with hematological indicators. Among them, only rs35289401 (CCDC157) was significantly associated (genome-wide) with red blood cell distribution width (RDW) (p = 4.21E-08). The fourteen top SNVs were selected for replication verification and were significantly associated with hematological phenotypes. However, only HBS1 L-MYB rs1331309 was significantly associated with the mean hemoglobin content (p = 6.42E-07). We also found that the mean corpuscular hemoglobin (MCH) level in the rs1331309 GG/GT genotype was significantly higher than that in the TT genotype (p = 0.023).Conclusion: The GWAS identified a total of 90 genetic variants significantly associated with hematological phenotypic indicators. In particular, rs1331309 (HBS1 L-MYB) is expected to be a biomarker for monitoring the dynamics of MCH levels. This study provides a reference for related studies on the genetic structure of hematological characteristics. It provides a valuable reference for the clinical diagnosis or prediction of a variety of diseases.Keywords: hematological, GWAS, hematological phenotype, MCH, Han population from northwest China